Keyword Technique as a Strategy for Vocabulary Development - Siagian, Khairul Azmi; Barus, Ricky Drimarcha; Lia Lisyati (Lembaga Pengembangan Kinerja Dosen, 2026)
Vocabulary acquisition is fundamental to language proficiency, yet retention remains a persistent cognitive challenge for students. Conventional rote-learning strategies often fail to facilitate long-term recall. This study examines the effectiveness of the keyword technique in improving students’ vocabulary mastery. Employing a quantitative quasi-experimental design, the research involved 48 students selected through cluster random sampling. The samples were separated into two groups: an experimental group of 26 students (taught by using the keyword technique) and a control group of 22 students (taught by using conventional strategy). Data were collected using a validated multiple-choice vocabulary test administered before and after the treatment. This result validates a notable difference in outcomes where the experimental group demonstrated better performance; consequently, the alternative hypothesis (Ha) is accepted, leading to the rejection of the null hypothesis (H0). These findings confirm that the Keyword Technique significantly enhances vocabulary mastery by leveraging acoustic and imagery associations. Consequently, this strategy is recommended to foster more effective vocabulary retention.